Filtro híbrido de dupla sintonia a quatro fios e a quatro braços - Morais, Ernande Eugenio Campelo (2014)
The modernization process has increased the use of loads with strongly non-linear characteristic. This situation is leading engineers to review the concepts of energy efficiency and power quality, in order to conciliate these two definitions. Then, the concept of power conditioning intrinsic to the power quality appears to be an interesting solution. With this concept, the solutions are designed to meet characteristics such as harmonics compensation and power factor correction, in order to ensure an electrical system that provides conditions for maximum energy efficiency of loads connected to the grid. Then arise passive filters and active as the most common solutions, both in practice and in the scientific and technical literature, with each other their advantages and disadvantages. Seeking to benefit from the advantages of both solutions, this work proposes the study and design of a hybrid filter. The proposed structure named dual tune hybrid filter allows the dissociation of the active stage from the passive stage, giving greater autonomy and practicality to the filter during replacement or maintenance operations in the active stage. This work also proposes a design methodology for the passive power stage, as well as the modeling and control of the active filter power stage. Because it is a new hybrid structure, it is made comparative analysis between the proposed hybrid power filter and shunt hybrid power filter, with the series converter with the passive filter, in order to validate the performance and its lower rated for the active stage with respect to the transformer in which it will be connected. Through modeling and design of the proposed hybrid filter, were obtained from a test case, satisfactory results as the correction of power factor and minimizing harmonic distortion voltage and current forward technical standards existing. These results validate the hybrid filter as an economically viable solution for improving the power quality of a distribution system at low voltage.